Social Justice and the Future of Higher Education Kinesiology. Issue 3 (2nd July 2016) - Culp, Brian
ABSTRACT: This article presents a rationale for the infusion of social justice into kinesiology programs for the purpose of reducing inequities in society. Specifically, the current climate for social justice is considered and discussed using examples from an university-inspired service-learning initiative, law, and politics. Of note are the following areas of discussion: (a) differentiation between social diversity and social justice, (b) public pedagogy as a means by which to inspire service action, (c) the creation of climates for speech and application of social justice, (d) modeling and socialization for equity, and (e) the neoliberal threat to inclusiveness. The article concludes with suggestions for practice, research, and training to implore kinesiology programs to position movement as an issue of justice.